Brilliant effect of Ca substitution in the appearance of magnetic memory in Dy0.5(Sr1−xCax)0.5MnO3 (x = 0.3) manganites. (October 2017) - Hamdi, R.; Tozri, A.; Dhahri, E.; Bessais, L.
Abstract: The present work undertakes an investigation of magnetic memory effect in Dy0.5 (Sr1−x Cax )0.5 MnO3 (x = 0 and x = 0.3) nanoparticles heated at 700 °C and 1350 °C. Zero-field-cooled (ZFC) and field-cooled (FC) magnetization measurements displayed the existence of magnetic memory effect in only samples with a Ca concentration x = 0.3. However, there is no sign of magnetic memory in samples with x = 0 of Ca amount. This confirms that the effect of substituting the Sr by Ca on the appearance of magnetic memory is of great importance, admitting that magnetic memory is mainly due to the powerful inter-particle interactions. Graphical abstract: Thermal variation of ZFC magnetization indicating the appearance of magnetic memory effect while substituting the Sr by Ca in Dy0.5 (Sr1−x Cax )0.5 MnO3 (x = 0.3) heated at 1350 °C. Highlights: Substituting Sr by Ca leads to the appearance of magnetic memory in Dy0.5(Sr1-xCax)0.5MnO3 (x = 0.3).